2015
DOI: 10.1038/nrcardio.2015.91
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risks and benefits of moderate and heavy alcohol consumption

Abstract: The heart and vascular system are susceptible to the harmful effects of alcohol. Alcohol is an active toxin that undergoes widespread diffusion throughout the body, causing multiple synchronous and synergistic effects. Alcohol consumption decreases myocardial contractility and induces arrhythmias and dilated cardiomyopathy, resulting in progressive cardiovascular dysfunction and structural damage. Alcohol, whether at binge doses or a high cumulative lifetime consumption-both of which should be discouraged-is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
260
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(279 citation statements)
references
References 179 publications
(305 reference statements)
5
260
1
13
Order By: Relevance
“…The health effects of drinking depend on the quantity and pattern of alcohol consumption. Although several studies have showed that light to modest alcohol consumption (especially wine or beer) is linked to a decrease in cardiovascular events and total mortality [1,2], some studies indicated that the relationship between alcohol consumption and several cardiovascular diseases is uncertain or negative even at moderate intakes [3][4][5]. Furthermore, excessive alcohol consumption adversely affects human health.…”
Section: Introductionmentioning
confidence: 99%
“…The health effects of drinking depend on the quantity and pattern of alcohol consumption. Although several studies have showed that light to modest alcohol consumption (especially wine or beer) is linked to a decrease in cardiovascular events and total mortality [1,2], some studies indicated that the relationship between alcohol consumption and several cardiovascular diseases is uncertain or negative even at moderate intakes [3][4][5]. Furthermore, excessive alcohol consumption adversely affects human health.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, compared to men, women show a significantly steeper doserelated inverse relationship between LVEF and TLDE [18]. This means that at a given dose of ethanol consumption, contractile LV function in women will be significantly lower than in men [2,3].…”
Section: Gendermentioning
confidence: 90%
“…One one hand, there is a pleasant tonic and healthy cardiovascular effect when consumed at occasional low doses in a social context, decreasing, for instance, cardiovascular morbidity and mortality [1]. On the other hand, alcohol is a toxic able to induce a variety of noxious cardiac and vascular effects when consumed in binges or at a high-cumulated lifetime consumption, increasing cardiovascular morbidity and mortality [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wine is one the most widely consumed beverages of the world and several health benefits have been suggested to result from its moderate consumption (41). There are many varieties of wine according to their organoleptic characteristics such as aroma, flavour and colour to name a few and those characteristics are attributed to its geographical location, growing conditions and fermentation processes (42).…”
Section: Food Composition Organoleptic Properties and Food Safetymentioning
confidence: 99%